Consular cooperation in third states: Some aspects concerning europanisation of foreign service for EU citizens - Erzsébet Csatlós (Bratislava Law Review, 2017)
The EU does not aim to harmonize the public administration of Member States, although, in recent years, there have been several examples which prove that EU legislation in whatever policy inevitably and unavoidably results in some standardization. In 2015 the EU replaced its former decision with a directive to enhance Member States to co-ordinate consular assistance in third States. Every EU citizen has the right to enjoy, in the territory of a third State in which the Member State of which they are nationals is not represented, the protection of the diplomatic and consular authorities of any Member State on the same conditions as the nationals of that State. This provision of Article 23 of TFEU not solely requires the cooperation of administrative authorities of foreign service but implicitly means a kind of harmonization of substantive law, leads to organizational changes and affects administrative procedural rules of Member States.